Oxygen production by intermediate metal sulphates in sulphur based thermochemical water splitting cycles. (22nd March 2015) - Tizzoni, A.C.; Corsaro, N.; D'Ottavi, C.; Licoccia, S.; Sau, S.; Tarquini, P.
Abstract: Thermochemical water splitting cycles, where the H2 O molecule is converted into hydrogen and oxygen by using recyclable and in general inorganic compounds as intermediates, basically consist of two separate sections, where, respectively, hydrogen and oxygen are produced. The most investigated cycles are based on the employment of sulphur containing species; generally, they differs with respect to how hydrogen is produced, but, basically, the step for oxygen formation is invariably a thermo-catalytical solar powered SO3 decomposition. Despite several important studies were dedicated to the development of a solar reactor for this task, the manageability of a solar receiver plant presenting a corrosive acid at high temperature is still a problematic issue. With the main target to reduce the materials cost of the necessary equipment, an intermediate metal oxide is employed; it is reacted with sulphuric acid or ammonium sulphate (according to the cycle considered) to produce the correspondent metal sulphate, which, in turn, is decomposed into sulphur dioxide and oxygen. The present article describes the experimental results obtained for each cycle step, two oxide/sulphate (iron (III) and Zn) systems are used and compared, and, all considered, the couple zinc oxide/sulphate appears to be the most feasible for the process, though, the use of iron (III) sulphate would allow to operate the process at a maximum temperature below 700 °C. A mass and thermal balances analysis for the proposed oxygen production steps were carried out, and results are compared with the reported values where sulphuric acid is directly decomposed, with a final discussion about advantages and drawbacks of both methods. Highlights: Thermochemical cycles: alternative route for oxygen production. Qualitative selection of the most feasible metal sulphates: ZnSO4, Fe2 (SO4 )3 . Reaction between Fe2 O3 and ZnO with (NH4 )2 SO4 or H2 SO4 : thermochemical analysis. Metal sulphates decomposition: thermodynamics and kinetics characterization. Thermal duties calculations for the alternative oxygen method proposed.